Identification of protease m1 zinc metalloprotease conferring resistance to deltamethrin by characterization of an AFLP marker in Culex pipiens pallens. Issue 1 (December 2016) - Zou, FF; Guo, Q; Sun, Y; Zhou, D; Hu, MX; Hu, HX; Liu, BQ; Tian, MM; Liu, XM; Li, XX; Ma, L; Shen, B; et al.
Abstract Background Continuous and excessive application of deltamethrin (DM) has resulted in the rapid development of insecticide resistance inCulex pipiens pallens . The quantitative trait loci (QTL) responsible for resistance to DM had previously been detected inCx. pipiens pallens . But locating the QTLs on the chromosomes remained difficult. An available approach is to first characterize DNA molecular markers linked with the phenotype, and then identify candidate genes. Methods In this study, the amplified fragment length polymorphism (AFLP) marker L3A8.177 associated with the QTL, was characterized. We searched for potential candidate genes in the flank region of L3A8.177 in the genome sequence of the closely relatedCx. pipiens quinquefasciatus and conducted mRNA expression analysis of the candidate genevia quantitative real-time PCR. Then the relationship between DM resistance and the candidate gene was identified using RNAi and American CDC Bottle Bioassay in vivo. We also cloned the ORF sequences of the candidate gene from both susceptible and resistant mosquitoes. Results The genesCYP6CP1 andprotease m1 zinc metalloprotease were in the flank region of L3A8.177 and had significantly different expression levels between susceptible and resistant strains.Protease m1 zinc metalloprotease was significantly up-regulated in the susceptible strains compared with the resistant and remained over-expressed in the susceptible field-collected strains. For deduced amino acid sequences ofprotease m1 zinc metalloprotease, there was no difference between susceptible and resistant mosquitoes. Knockdown ofprotease m1 zinc metalloprotease not only decreased the sensitivity of mosquitoes to DM in the susceptible strain but also increased the expression ofCYP6CP1, suggesting the role ofprotease m1 zinc metalloprotease in resistance may be involved in the regulation of the P450 gene expression. Conclusion Our study represents an example of candidate genes derived from the AFLP marker associated with the QTL and provides the first evidence thatprotease m1 zinc metalloprotease may play a role in the regulation of DM resistance inCx. pipiens pallens .